Upaya Program Studi Dalam Menyiapkan Lulusan Berkompeten Sesuai Kerangka Kualifikasi Nasional Indonesia (KKNI) (Studi pada Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Muhammadiyah Surakarta Tahun 2016) - Wigati, Woro Ayu; , Drs. Marpuji Ali, M.SI (2016)
This research has the background that the Indonesia National Qualifications Framework (INQF) is a level framework of qualification of competence to reconcile, equalize, and integrate the fields of education and vocational training, which will be a reference in the curriculum and quality assurance of education. The purpose of the research is to describe efforts of Islamic Education Departement (IED) of the Faculty of Islamic Studies (FIS) Universitas Muhammadiyah Surakarta (UMS), in preparing graduates being competent according INQF, as well as the supporting and resisting factors. This research is a field research, using qualitative descriptive approach, applying the method of observation, interview and documentation in data collection, and implementating the interactive method in qualitative data analysis. Based on the study of theory, research data and analysis being done, then the conclusion is that IED seeks to prepare graduates who are competent in accordance with the INQF with an effort to redefine the vision, mission, goals and graduate profile and to formulate learning outcomes referring to INQF, and to provide education courses, practicing self-discipline and responsibility of the student. The supporting factors in setting up competent graduates with INQF, among others are: the policy of the university; the readiness of lecturers and adequate facilities; and providing incentives to students who work. The resisting factor are the system of implementating the final evaluation being organized in a decentralized manner, but centrally by the Academic Administration Bureau UMS; the low achievement of input students in the IED, and the large number of students during the learning process in the classroom resulting in diminishing the learning effectiveness. Keywords: Indonesia National Qualifications Framework, Graduates are Competent, Departement.